THE COMPARATIVE ANALYSIS OF STOMATOLOGIC DISEASE OF CHILDREN OF THE ІVANO-FRANKIVSK REGION - Лучинський, М. А.; Октисюк, Ю. В.; Лучинський, А. М.; Гончар, Ю. І.; Лучинський, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In article given the data about stomatologic level of health of 7-15 years old children in Ivano-Frankovsk area which reside in different klimato geographical conditions. It is shown that stomatologic level of health tends to decrease from 83 % at 7-years old children to 59 % at 15-years old teenagers. There are not revealed authentic differences of stomatologic level of health at children who live in different klimato-geographical regions. Average index DNF of the teeth at 9-year-old children who live in flat сountry is on 0.55 lesser (p <0.05), than in the mountain. There are small differences of intensity of dental caries also at children of 12 and 15 years.